A framework for regression-based inference of candidate genes causal to salt tolerance in rice - Yap, Jan Michael C. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
An important task in genetics research is to be able to generate a set of candidate genes causal towards expression of a particular trait. In the work presented here, a framework utilizing regression-based inference of candidate genes causal to salt tolerance in rice is proposed. The framework integrates market data, quantitative trait loci data, gene expression and genome region data, and phenotypic data to generate the set of candidate genes. Results suggest 91 genes to be potentially causal to salt tolerance in rice. Review of literature substantiated the results in mentioning the role of genes related to cell wall and membrane-related function, and signal transduction-related functions to salt tolerance in rice. Proof of the algorithmic correctness of the implementation has time complexity O(ngm + g^2 + n^3 + 2^p), while the space complexity is O(n(m + g +q) + g^2), where n is the number of individuals, g is the number of genes, p is the number of the genes to be considered for candidate causal gene selection where 1 ≤ p < g, m is the number of markers used as input, and q is the number of quantitative trait loci associated with the trait.
Thesis (Ph.D. Computer Science)--University of the Philippines, Diliman.
Keywords: Regression analysis; Rice -- Effect of salt on -- Philippines; Integrative genomics